2018
DOI: 10.1007/s00520-018-4235-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the EPIPHANY index for predicting risk of serious complications in cancer patients with incidental pulmonary embolism

Abstract: Our study suggests the EPIPHANY index could be a useful adjunct tool in risk stratification of cancer patients with IPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Third, the capacity to discriminate prognosis in incidental episodes is one of the most noteworthy contributions, since the rest of the scores were designed for acute, symptomatic PE [37] and do not contain the variables that make it possible to discriminate levels of risk within unsuspected PE. Our results are consistent with the retrospective validation by Ahn et al, focused on incidental PE, that reported a 15-day complication rate of 3.4, 8.9, and 23.8% for low-, intermediate-, and high-risk EPIPHANY episodes [28]. In return, the EPIPHANY Index/Hestia criteria perform worse in acute, symptomatic PE, as patients in this scenario are rarely classified as low risk.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Third, the capacity to discriminate prognosis in incidental episodes is one of the most noteworthy contributions, since the rest of the scores were designed for acute, symptomatic PE [37] and do not contain the variables that make it possible to discriminate levels of risk within unsuspected PE. Our results are consistent with the retrospective validation by Ahn et al, focused on incidental PE, that reported a 15-day complication rate of 3.4, 8.9, and 23.8% for low-, intermediate-, and high-risk EPIPHANY episodes [28]. In return, the EPIPHANY Index/Hestia criteria perform worse in acute, symptomatic PE, as patients in this scenario are rarely classified as low risk.…”
Section: Discussionsupporting
confidence: 91%
“…for low-, intermediate-, and high-risk EPIPHANY episodes [28]. In return, the EPIPHANY Index/Hestia criteria perform worse in acute, symptomatic PE, as patients in this scenario are rarely classified as low risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individualized management of acute cancer presentations is essential in emergency oncology services so it can mirror routine cancer care [57]. The spectrum of emergency cancer presentations is increasing and includes not only FN but also incidental pulmonary embolism, indwelling line infections, and chemotherapy-related acute kidney injury, which can be risk assessed for care in these settings [57][58][59].…”
Section: Expanded Use Of Granulocyte Colony-stimulating Factor Duringmentioning
confidence: 99%
“…The EPIPHANY index may be a useful adjunct tool in supporting physicians considering outpatient management for cancer patients with IPE. [17] Cancerassociated DVT is another important presentation suitable for ambulatory management.…”
Section: Ambulatory Emergency Oncology Presentationsmentioning
confidence: 99%